Pengalaman Remaja dari Keluarga Broken Home dalam Menghadapi Trauma Masa Kecil - Putri Balqis; Sri Nurhayati Selian (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The family is the primary and primary environment that plays a crucial role in shaping a child's personality, emotional development, and psychological stability. Through the family, children receive love, a sense of security, and values ​​that form the basis for developing their identity. However, broken homes can disrupt a child's emotional balance and lead to childhood trauma that impacts them into adolescence. This study aims to understand the experiences of adolescents from broken homes in coping with childhood trauma and the process of building resilience. The method used was a qualitative approach with a descriptive research type. The study subjects consisted of three adolescents aged 20–23 who experienced broken families since childhood. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive analysis model through the stages of data reduction, data presentation, and conclusion drawing. The results showed that childhood trauma emerged in the form of emotional, relational, physical, and existential trauma due to the loss of parental figures, conflict, emotional neglect, and verbal abuse. The impacts felt include low self-confidence, anxiety, mild depression, and difficulty relating to social relationships. Social support from extended family, friends, and the community has been shown to aid the recovery process and increase resilience. This study emphasizes the important role of parents, educators, and counselors in providing emotional support and a safe environment for adolescents from broken homes.